Reimplante tardío de un incisivo central superior avulsionado: reporte de caso (2018)
The most severe dento-alveolar trauma is dental avulsion, its forecast is questionable in many cases. Dental reimplantation is a challenge for the dentist, due to the strict management and strict fulfilment of protocols that can determine a successful long-term outcome. This case report shows a 5-years clinical and radiographic follow-up of an avulsed right maxillary central incisor reimplanted 7 hours later in a 16-year-old teenager from Bucaramanga. The evolution of the case showed a positive status in spite of the limited conditions of time and conservation of the tooth.